2011
DOI: 10.1063/1.3644840
|View full text |Cite
|
Sign up to set email alerts
|

The destabilization of an initially thick liquid sheet edge

Abstract: International audienceBy forcing the sudden dewetting of a free soap film attached on one edge to a straight solid wire, we study the recession and subsequent destabilization of its free edge. The newly formed rim bordering the sheet is initially thicker than the film to which it is attached, because of the Plateau border preexisting on the wire. The initial condition is thus that of an immobile massive toroidal rim connected to a thin liquid film of thickness h. The terminal Taylor-Culick receding velocity V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…This timescale is identical to that of the Rayleigh-Plateau instability, as already observed for liquid sheet edges in a different context by Lhuissier & Villermaux (2011). Figure 10 shows that (5.1) is in excellent agreement with the experimental data with a prefactor of 1.1.…”
Section: (B)supporting
confidence: 84%
“…This timescale is identical to that of the Rayleigh-Plateau instability, as already observed for liquid sheet edges in a different context by Lhuissier & Villermaux (2011). Figure 10 shows that (5.1) is in excellent agreement with the experimental data with a prefactor of 1.1.…”
Section: (B)supporting
confidence: 84%
“…Here σ is the surface tension, ρ the liquid density, and δ the air sheet thickness. This is essentially the same as for liquid sheets in air [11][12][13][14][15][16][17]. By using this result and assuming that the disk remains of uniform but growing thickness δ(t) during the contraction, it is found that the radius of the air disk R(t) reduces exponentially in time [3,4] …”
mentioning
confidence: 50%
“…When viscous effects can be neglected, the velocity of the edge can be estimated by the Taylor-Culick velocity u σ = √ 2σ/(ρδ): see Oguz & Prosperetti (1989), Brenner & Gueyffier (1999), Song & Tryggvason (1999), Lhuissier & Villermaux (2011) and Gordillo et al (2011). This approximation is valid for films thicker than δ = 2µ 2 /(ρσ ).…”
Section: Film Thickness and Speed Of Rupturementioning
confidence: 99%